Bipolar-assisted tonsil reduction: a simple and inexpensive tonsillotomy technique - Çağdaş Kazıkdaş, Kadir; Asım Şafak, Mustafa (ENT Updates, 2018)
Objective: This study aims to investigate the novel use of a simple and inexpensive bipolar-assisted tonsil reduction (B-TR) technique in pediatric cases with adenotonsillar hyperplasia by evaluating long-term results, possible complications, need for reoperation and incidence of recurrence. Methods: We present our long-term retrospective data from 78 consecutive pediatric cases undergoing B-TR combined with adenoidectomy from April 2013 to January 2017. The tonsillar sizes were recorded using the Brodsky grading scale from I to IV, and the patients only with prominant tonsillar sizes (III and higher) and adenoidal sizes exceeding 50% were included in the study group. The tonsil sizes were noted preoperatively, and during the latest follow-up visit after tonsillotomy (min. 9 months postoperatively). Results: With a mean follow-up period of 18.3 months, the mean tonsillar size preoperatively was 3.47 (±0.50) and mean tonsillar size postoperatively was 1.35 (±0.48). A significant difference (p<0.001) was observed between these two groups, excluding the only case who later had undergone tonsillectomy. Minimal uvular edema was noted in 27 children (34.6%), which did not cause any upper airway obstruction in these patients. Conclusion: We describe herein our B-TR technique in details so that it can be learned relatively quickly and used in pediatric cases with adenotonsillar hyperplasia as a treatment option.